Induction motor bearing failure detection and diagnosis: Park and concordia transform approaches comparative study - Onel, Izzet Yilmaz; Benbouzid, Mohamed El Hachemi (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2008)
This paper deals with the problem of bearing failure detection and diagnosis in induction motors. Indeed, bearing deterioration is now the main cause of induction motor rotor failures. In this context, two fault detection and diagnosis techniques, namely the Park transform approach and the Concordia transform, are briefly presented and compared. Experimental tests, on a 0.75 kW two-pole induction motor with artificial bearing damage, outline the main features of the aforementioned approaches for small- and medium-size induction motors bearing failure detection and/or diagnosis.
Keywords: bearing failure; concordia transform; diagnosis; fault detection; induction motor; park transform; ROLLING ELEMENT BEARINGS; WINDING FAULT-DIAGNOSIS; STATOR CURRENT; DAMAGE DETECTION; VECTOR; SYSTEM; DRIVE; Automation & Control Systems; Engineering